Agent-based computational models - Flache, Andreas (Research Handbooks in Sociology series, 2021)
Agent-based computational modeling (ABCM) plays a central role in Analytical Sociology (AS). ABCM attracts analytical sociologists because it combines analytic precision, ability to capture complex micro-macro interactions and flexibility to accommodate empirically realistic assumptions. This chapter gives readers an easily accessible introduction to ABCM in the context of AS. We provide and elaborate a modelling example the reader can download and replicate. Schelling's well-known model of segregation is progressively extended towards including empirically more realistic assumptions. The example is used to illustrate the use of 10 good practices we propose in this chapter for ABCM in the context of AS. We demonstrate how it can be challenging to understand what the consequences are of adding realism to an abstract model, and how ABCM - if properly used - is a powerful instrument for developing full comprehension of the complex dynamics generated by the computational implementation of a social mechanism.